NEGOTIATE PERSUADE AND CREATE GREAT DEALS - Benoliel, Michael; Mukherjee, Geetanjali; Yong, Jose Jin Chuan (Singapore : World Scientific Publishing Co Pte Ltd., 2020)
Negotiation comes up in our daily lives in so many interactions - in job interviews, while buying a house, and even when deciding where to go on a date or discussing your teenager's curfew. Executives are routinely expected to negotiate - with vendors, customers and each other - with little training or experience. Companies rely on their people to negotiate multi-million dollar deals, but fail to provide even basic negotiation tools.Negotiate, Persuade and Create Great Deals brings together cutting-edge research on negotiation from neuroscience, evolutionary theory and behavioral psychology along with interviews and insights with 25 master negotiators in business, politics, sports and diplomacy. We provide tools and techniques that can help executives and business professionals improve their ability to negotiate deals, while also laying out a framework that can support companies that wish to improve their organizational negotiation capabilities. Blending theory and practice, with plenty of examples of successful and failed negotiations in business and politics, this practical guide is an invaluable tool to prepare you for your next negotiation.
Keywords: Business planning; Strategic planning